Implementation and analysis of PANET - Yu-xuan1 ZHANG; Shen YAN; Xi-wei XU (Tongxin xuebao)
Partial-state asymmetric NAT (PANAT) could translate any prefixes of IPv6 address seamlessly.With the implementation of PANAT method by using Netfilter framework,it does both the quantitative research and qualitative research for PANET.Some suggestions are given for using PANET in the real environment though comparison of the translation efficiency and the hosts scales.